Ultraviolet, visible and near-infrared hard antireflection film
By alternately aligning the hydrogen-doped silicon nitride film and low refractive index film layers on the optical substrate, a silicon nitride (SiNx:H) film with high hardness and ultraviolet low absorption was prepared, which solved the problem that the ultraviolet band hard anti-reflective film in the prior art is difficult to meet the high hardness, low absorption and high transmittance at the same time, and achieved excellent optical and mechanical properties in the ultraviolet band.
Patent Information
- Application Number
- CN202411727204.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-04-08
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art is difficult to meet the performance requirements of high hardness, low absorption and high transmittance of hard anti-reflective films in the ultraviolet band, especially in the fields of ultraviolet lithography and photodetectors.
By alternately aligning the hydrogen-doped silicon nitride film and the low refractive index film layer on the optical substrate, a silicon nitride (SiNx:H) film with high hardness and ultraviolet low absorption was prepared by using argon sputtering and radio frequency plasma source assisted reaction gases.
High transmittance and mechanical properties in the ultraviolet band 250-400nm range were achieved, the film hardness reached 18-26GPa, and the extinction coefficient was lower than 0.002 in the 300nm band, which significantly improved the transmittance and mechanical stability of the optical system.
Smart Images

Figure CN119781095A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of optical elements, and in particular relates to an ultraviolet, visible and near-infrared hard anti-reflection film. Background Art
[0002] The hardness of the film is an important physical property, which comes from the interaction of interatomic forces. The hardness of the film layer is directly related to the macroscopic performances such as scratch resistance, wear, and durability. Improving the hardness of the optical film helps to improve the scratch resistance and wear resistance of the optical film, and greatly improves the service life of the optical film element.
[0003] In the visible light band, there are relatively more hard film materials to choose from. For example, the Si3N4 film prepared by the sputtering method has low absorption in the visible region and a high refractive index of 2.05. At the same time, the hardness is as high as 22GPa, which is very hard, durable and corrosion-resistant. 3 N 4 / SiO 2 The stacked hard anti-reflection films in the visible light band have received widespread attention and are widely used in the field of consumer electronics.
[0004] When extended to the ultraviolet band, commonly used optical thin film materials include LaF 3 MgF 2 , AlF 3 Fluoride and Al 2 O 3 Sc 2 O 3 , HfO 2 、SiO 2 However, the hardness of these fluorides and oxides is much lower than that of nitrides, and the scratch problem of UV optical films during use, packaging, wiping and cleaning needs to be paid special attention.
[0005] The hardness of nitride film is almost twice that of oxide, which can withstand the wiping and wear during daily use, significantly improving the service life of optical film components. However, the hard film materials in the visible region are no longer applicable in the ultraviolet band. For example, Si 3 N 4 Hard films such as AlN and Ta-C are not transparent in the ultraviolet band and have significant absorption below 400nm wavelength. Although there are literatures showing that hydrogen-doped silicon nitride has reduced ultraviolet absorption, there are still obstacles to its practical application in the field of optical coating. Taking LPCVD (low pressure chemical vapor deposition) and PECVD (plasma enhanced chemical vapor deposition) deposition methods as examples, these two methods cannot achieve precise control of hydrogen content, and hydrogen is often introduced into Si as a by-product. 3 N 4 In the membrane layer.
[0006] For example, the PECVD (plasma enhanced chemical vapor deposition) method disclosed in the literature "Journal of Applied Physics (IF 2.7) Pub Date: 1991-08-01, DOI: 10.1063 / 1.349544, Low hydrogen content stoichiometric silicon nitride films deposited by plasma-enhanced chemical vapor deposition" can deposit Si at a lower temperature. 3 N 4 Thin films, however, Si prepared by PECVD process 3 N 4 The film contains a high proportion of hydrogen (20-35%). A large amount of hydrogen atoms will not only reduce the hardness and stability of the film, but also escape from the film under high temperature conditions, causing structural changes and degradation of optical properties of the film. Therefore, low hydrogen content SiN x The preparation of :H thin films is the focus of the research. This PECVD method has significant challenges in accurately controlling the hydrogen content while maintaining high-precision film control, and is also not used in the field of precision optical coatings.
[0007] In summary, although Si 3 N 4 The film exhibits good mechanical strength and damage resistance in the visible and near-infrared bands, but its high absorption in the ultraviolet band limits its application in broad-spectrum optical systems, especially in the fields of ultraviolet lithography and ultraviolet photodetectors. 3 N 4 The film cannot provide sufficient transmittance. In addition, the ultraviolet, visible and near-infrared bands have put forward higher requirements for the demand for hard anti-reflection films. The existing technology cannot simultaneously meet the performance requirements of high hardness, low absorption and high transmittance in the wide spectrum range from ultraviolet to near-infrared. Summary of the invention
[0008] The invention provides an ultraviolet, visible and near-infrared hard anti-reflection film, which has high transmittance and mechanical properties in the ultraviolet, visible and near-infrared bands.
[0009] The present invention provides an ultraviolet, visible and near-infrared hard anti-reflection film, comprising hydrogen-doped silicon nitride thin films and low refractive index film layers alternately arranged on an optical substrate;
[0010] Wherein, the thickness of the hydrogen-doped silicon nitride film accounts for more than 70% of the thickness of the hard anti-reflection film;
[0011] The total thickness of the hard anti-reflection film is 500-2500nm;
[0012] The hydrogen-doped silicon nitride film is prepared by the following method, comprising:
[0013] Sputtering of silicon target by argon gas;
[0014] Then, a radio frequency plasma source is used to assist the reaction gas, so that a hydrogen-doped silicon nitride film is formed on the substrate. The reaction gas is H 2 and N 2 , H 2 The flow rate is 5-100sccm.
[0015] The hydrogenated silicon nitride (SiNx:H) film proposed in the present invention has the advantages of high hardness and low ultraviolet absorption. By using the method of adding hydrogen in the post-reaction sputtering process and adjusting the ratio of hydrogen, nitrogen and argon, the refractive index, extinction coefficient, residual stress and hardness of the film can be precisely controlled. This method breaks through the inherent ultraviolet absorption limitation of silicon nitride film (SiNx), and the transparent window is expanded to the ultraviolet band of 250-400nm.
[0016] Preferably, the H 2 The flow rate is 40-80 sccm. By controlling the hydrogen flow rate, the hydrogenated silicon nitride (SiNx:H) film has good low ultraviolet absorption and maintained high hardness properties.
[0017] Preferably, the flow rate of the argon gas is 50-150 sccm.
[0018] Further preferably, the flow ratio of hydrogen to nitrogen is 0.2-1.
[0019] The present invention controls the flow ratio of the reactive nitrogen and hydrogen, thereby ensuring sufficient hydrogen doping to ensure the permeability of the SiNx:H film and preventing excessive hydrogen doping from reducing the hardness of the film, thereby overcoming the problem of CVD deposition of Si 3 N 4 Hydrogen in the film will have an adverse effect on the mechanical stability of the film, resulting in a decrease in the density of the film and a decrease in hardness.
[0020] The hydrogen-doped silicon nitride film provided by the present invention has a hardness of 18-26 GPa and an elastic modulus of 170-230 GPa; in the 300 nm band, the extinction coefficient of the hydrogen-doped silicon nitride film is <0.002. Further preferably, the refractive index interval ranges from 1.75 to 2.05 @ 550 nm.
[0021] Preferably, the hydrogen-doped silicon nitride film is a film layer with a refractive index of ≥1.7, and the low-refractive-index film layer is a film layer with a refractive index of ≤1.6.
[0022] Preferably, the thickness of the hydrogen-doped silicon nitride film accounts for 80-95% of the thickness of the hard anti-reflection film. The present invention greatly improves the hardness and wear and scratch resistance of the film by increasing the proportion of the hydrogen-doped silicon nitride film, a high-hardness, high-refractive index film material, in the total thickness.
[0023] Preferably, the total thickness of the hard anti-reflection film is 1000-2000 nm.
[0024] Further preferably, the hardness of the hard anti-reflection film is >15 GPa.
[0025] Further preferably, in the wavelength range of 300-1100 nm, Rave<2%+Tave>97% of the hard anti-reflection film.
[0026] Further preferably, in the wavelength band of 300-400 nm, Rave<0.5%+Tave>99% of the hard anti-reflection film.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] (1) The hydrogenated silicon nitride (SiNx:H) film prepared by the method of the present invention has high hardness and significantly reduced extinction coefficient in the ultraviolet band (250-400nm). Compared with the traditional silicon nitride film (transmittance is only 65.5%), the hydrogenated silicon nitride (SiNx:H) film prepared by the present invention can increase the transmittance of the film to more than 90% at a wavelength of 270nm, greatly reducing the absorption loss in the optical system.
[0029] (2) The content of hydrogen components in the low-hydrogen-doped nitride film prepared by the method provided in the specific embodiment of the present invention can be precisely controlled by process regulation during the preparation process, while the chemical vapor deposition method disclosed in the prior art is difficult to achieve precise control of the hydrogen content.
[0030] (3) The UV, visible, and near-infrared hard anti-reflection film of the present invention has an average transmittance of more than 98% in the 300-1100nm band; the maximum hardness can reach more than 15GPa. The UV hard anti-reflection film prepared by this method has an average transmittance of more than 99% in the 300-400nm band; the maximum hardness can reach more than 15GPa, even up to more than 18GPa, and has very excellent spectral and mechanical properties. The hard anti-reflection film surpasses the traditional oxide-based anti-reflection film in terms of mechanical properties, and has broad application prospects in many fields such as UV photoelectric detectors, UV solar blind windows, spectrometers, astronomical system windows, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1This is a curve showing the effect of hydrogen content on transmittance in the SiNx:H film prepared in Example 1 of the present invention;
[0032] Figure 2 This is a curve showing the effect of hydrogen content on the refractive index and extinction coefficient in the SiNx:H film prepared in Example 1 of the present invention;
[0033] Figure 3 The hardness of the SiNx:H film obtained in Example 1 of the present invention; the flow rate of sputtering argon is controlled at 50-100 sccm, and the ratio of hydrogen to argon is controlled at 0.2-1 to obtain a higher hardness;
[0034] Figure 4 The elastic modulus of the SiNx:H film obtained in Example 1 of the present invention; the characteristic range of the elastic modulus is 170-230 GPa;
[0035] Figure 5 This is an optical transmittance curve of the hard anti-reflection film in the ultraviolet 300-400nm band prepared in Example 2 of the present invention;
[0036] Figure 6 This is an optical reflectivity curve of the hard anti-reflection film in the ultraviolet 300-400nm band prepared in Example 2 of the present invention;
[0037] Figure 7 This is the load-displacement curve of the hard anti-reflection film in the ultraviolet 300-400nm band prepared in Example 2 of the present invention; the hardness of the film layer is calculated by the Oliver & Pharr method.
[0038] Figure 8 This is a graph showing the optical transmittance of the hard anti-reflection film in the ultraviolet 300-1100nm band prepared in Example 2 of the present invention;
[0039] Fig. 9 This is an optical reflectivity curve of the hard anti-reflection film in the ultraviolet 300-1100nm band prepared in Example 2 of the present invention;
[0040] Fig.10 This is the load-displacement curve of the hard anti-reflection film in the ultraviolet 300-1100nm band prepared in Example 2 of the present invention; the hardness of the film layer is calculated by the Oliver & Pharr method. DETAILED DESCRIPTION
[0041] The present invention will be further described below in conjunction with the embodiments and drawings.
[0042] Example 1
[0043] (1) Substrate cleaning: Clean the JGS1 substrate and dry it;
[0044] (2) Deposition of SiNx:H film by post-reaction magnetron technology: First, the silicon target is sputtered by inert argon gas magnetron sputtering, and the silicon atoms bombarded form a SiNx film on the upper part of the substrate. Then, the RF plasma source ICP is used to assist the reaction gas H 2 and N 2 The film is subjected to a reaction treatment to form a corresponding hydrogen-doped silicon nitride film on the film. 2 The flow rate of hydrogen gas is fixed at 100 sccm. The hydrogen flow rates of SiNx:H films No. 1-6 are 0, 20, 40, 60, 80, and 100 sccm, respectively. The deposition rate of SiNx:H films during sputtering is 0.3-0.6 nm / s.
[0045] (3) Finish of coating:
[0046] a. A spectrometer was used to measure the transmittance of SiNx:H films under different hydrogen flow conditions. Figure 1 The graph is a graph showing the effect of hydrogen content on transmittance in SiNx:H films No. 1 to 6. As can be seen from the graph, the hydrogen-doped silicon nitride film obtained after hydrogen is introduced has a higher transmittance.
[0047] b. The optical constants and extinction coefficients are obtained by fitting the measured transmission and reflection spectra. Figure 2 The graph shows the effect of hydrogen content on the refractive index and extinction coefficient in SiNx:H films No. 1-6. There are significant differences in the optical properties of the films prepared by hydrogen-free (curve 1) and hydrogen-containing (curves 2-6) processes in the 250-400nm band.
[0048] c. The hardness of the SiNx:H film layer was measured using a high-precision nanoindenter with a test penetration depth of 50 nm to avoid the influence of the substrate hardness. Figure 3 The hardness of SiNx:H films was tested by nanoindentation, ranging from 18-26 GPa. Figure 4 is the elastic modulus of the SiNx:H film, ranging from 170 to 230 GPa. In order to obtain a higher hardness, the flow range of argon gas is preferably 50 to 100 sccm, and the ratio of hydrogen to argon gas is controlled between 0.2 and 1.
[0049] Example 2
[0050] This embodiment relates to a design and preparation method of a hard anti-reflection film, which is suitable for the ultraviolet 300-400nm band. The film has optical properties of low reflectivity and high transmittance, and mechanical properties of high hardness>15GPa and hard film layer height>70%.
[0051] (1) Film system design: According to the spectral performance requirements: Rave (reflectivity) <0.5% @ 300-400nm, Tave (transmittance) > 99% @ 300-400nm. The designed film system structure is shown in Table 1, where L represents the low refractive index material SiO 2 , H represents the high refractive index material SiNx:H prepared in Example 1. It can be understood that the refractive index of SiNx:H provided in Table 1 indirectly discloses the flow rate of hydrogen introduced when the prepared SiNx:H is prepared.
[0052] (2) Base cleaning: clean the base and dry it;
[0053] (3) Coating: For the above-mentioned film structure, a 300-400nm ultraviolet hard anti-reflection film is prepared by a post-reaction magnetron sputtering method.
[0054] (4) Finish of coating:
[0055] a. Use a spectrometer to measure the spectral performance of the UV hard anti-reflection film. Figure 5 and Figure 6 The optical transmittance and reflectivity curves of the hard anti-reflection film in the ultraviolet 300-400nm band are respectively. The present invention solves the problem of ultraviolet absorption limitation of traditional silicon nitride materials. Figure 5 and Figure 6 Based on the same method, the high refractive index material is Si 3 N 4 The transmittance and reflectance curves of the prepared anti-reflection film show that the anti-reflection film prepared in this embodiment has a higher transmittance and a lower reflectance.
[0056] b. Use a high-precision nanoindenter to measure the hardness of the UV hard anti-reflection film layer. Figure 7 The load displacement curve and indentation hardness of the UV hard anti-reflection film are shown in Figure 2. Compared with the oxide film commonly used in the traditional UV band, the hard anti-reflection film prepared in this embodiment has a hardness higher than 15
[0057] Indentation hardness in GPa.
[0058] Example 3
[0059] This embodiment relates to a design and preparation method of a hard anti-reflection film, which is suitable for ultraviolet, visible, and near-infrared 300-1100nm bands. The film has optical properties of low reflectivity and high transmittance, and mechanical properties of high hardness>15GPa and hard film layer height>70%.
[0060] (1) Film system design: According to the spectral performance requirements: Rave <2% @ 300-1100nm, the designed film system structure is shown in Table 2, where L represents the low refractive index material SiO2 , H represents the high refractive index material SiNx:H prepared in Example 1. It can be understood that the refractive index of SiNx:H provided in Table 1 indirectly discloses the flow rate of hydrogen introduced when the prepared SiNx:H is prepared.
[0061] (2) Base cleaning: clean the base and dry it;
[0062] (3) Coating: For the above-mentioned film structure, a 300-1100nm ultraviolet hard anti-reflection film is prepared by a post-reaction magnetron sputtering method.
[0063] (4) Finish of coating:
[0064] a. Use a spectrometer to measure the spectral performance of the UV hard anti-reflection film. Figure 8 and Fig. 9 They are the optical transmittance and reflectivity curves of the hard anti-reflection film in the 300-1100nm band. Figure 8 and Fig. 9 The same film system is used in both cases, and the high refractive index film layer uses Si 3 N 4 The optical transmittance and reflectivity curves of the anti-reflection film. The invention solves the ultraviolet absorption limitation problem of traditional silicon nitride materials.
[0065] The hardness of the UV hard anti-reflection film layer was measured using a high-precision nanoindenter. Fig.10 The load displacement curve and indentation hardness of the hard anti-reflection film in the 300-1100nm band are shown in Figure 1. Compared with the oxide film commonly used in the traditional ultraviolet band, the hard anti-reflection film proposed in this embodiment has an indentation hardness higher than 15 GPa.
[0066] Table 1. Structure of hard anti-reflection film in the UV 300-400nm band
[0067]
[0068] Table 2. Hard anti-reflection film structure in the UV, visible and near-infrared 300-1100nm band
[0069]
[0070]
Claims
1. A hard anti-reflection film for ultraviolet, visible and near infrared, characterized in that: The invention comprises hydrogen-doped silicon nitride thin films and low refractive index film layers alternately arranged on an optical substrate; Wherein, the thickness of the hydrogen-doped silicon nitride film accounts for more than 70% of the thickness of the hard anti-reflection film; The total thickness of the hard anti-reflection film is 500-2500nm; The hydrogen-doped silicon nitride film is prepared by the following method, comprising: Sputtering of silicon target by argon gas; Then, a radio frequency plasma source is used to assist the reaction gas so as to form a hydrogen-doped silicon nitride film on the substrate. The reaction gas is H2 and N2, and the flow rate of H2 is 5-100 sccm.
2. The ultraviolet, visible and near-infrared hard anti-reflection film according to claim 1, characterized in that: The flow rate of H2 is 40-80 sccm.
3. The ultraviolet, visible and near-infrared hard anti-reflection film according to claim 1, characterized in that: The flow rate of the argon gas is 50-150 sccm.
4. The ultraviolet, visible and near-infrared hard anti-reflection film according to claim 3, characterized in that: The flow rate of the argon gas is 50-100 sccm.
5. The ultraviolet, visible, and near-infrared hard anti-reflection film according to claim 1 or 4, characterized in that: The flow ratio of hydrogen to nitrogen is 0.2-1.
6. The ultraviolet, visible and near infrared hard anti-reflection film according to claim 5, characterized in that: The hardness of the hydrogen-doped silicon nitride film is 18-26 GPa, and the elastic modulus is 170-230 GPa; in the 300 nm wave band, the extinction coefficient of the hydrogen-doped silicon nitride film is less than 0.
002.
7. The hard anti-reflection film according to claim 1, characterized in that: The total thickness of the hard anti-reflection film is 1000-2000nm.
8. The hard anti-reflection film according to claim 7, characterized in that: The hardness of the hard anti-reflection film is greater than 15 Gpa.
9. The hard anti-reflection film according to claim 7, characterized in that: In the wavelength range of 300-1100 nm, Rave<2%+Tave>97% of the hard anti-reflection film.
10. The hard anti-reflection film according to claim 9, characterized in that: In the 300-400 nm wavelength band, Rave<0.5%+Tave>99% of the hard anti-reflection film.
Citation Information
Patent Citations
Method for preparing passivation antireflection film on front surface of crystalline silicon solar battery
CN102569533A
Solar cell antireflection film and preparation method thereof
CN109713049A
Hard antireflection film and optical film product of visible light wave band
CN118859372A
Hydrophobic and ultraviolet radiation proof transparent film and preparation thereof
CN1594646A
Formation of silicon nitride thin film and apparatus for the same
JP1986053734A